2011
DOI: 10.1089/cyber.2010.0425
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Anxiety in Online Health Information Search

Abstract: This article is one of the first to empirically explore the relationship between health anxiety and online health information search. Two studies investigate how health anxiety influences the use of the Internet for health information and how health anxious individuals respond to online health information. An exploratory survey study with 104 Dutch participants indicates that health anxiety is related to an increase in online health information search. Moreover, results suggest that health anxious individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
192
8
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(232 citation statements)
references
References 32 publications
15
192
8
17
Order By: Relevance
“…Furthermore, negative emotions during searches were strongly associated with non-resolution of the search process, whereas positive emotions during searching were strongly linked to successful resolutions and search terminations, potentially leading to negatively reinforcing behaviour and the need for/lack of control in searching. This supports past research finding both relief (suggestive of successful resolution; Singh & Brown, 2014), and distress/tension/anxiety (suggesting non-resolution; Baumgartner & Hartmann, 2011;Muse et al, 2012;Singh & Brown, 2014, 2015 in high health anxious individuals post-search. It also relates to the type of information searched for, as well as the perceived seriousness and familiarity of the issue.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, negative emotions during searches were strongly associated with non-resolution of the search process, whereas positive emotions during searching were strongly linked to successful resolutions and search terminations, potentially leading to negatively reinforcing behaviour and the need for/lack of control in searching. This supports past research finding both relief (suggestive of successful resolution; Singh & Brown, 2014), and distress/tension/anxiety (suggesting non-resolution; Baumgartner & Hartmann, 2011;Muse et al, 2012;Singh & Brown, 2014, 2015 in high health anxious individuals post-search. It also relates to the type of information searched for, as well as the perceived seriousness and familiarity of the issue.…”
Section: Discussionsupporting
confidence: 89%
“…doctor advantages), suggesting that in some cases doctor disadvantages related to time and convenience were the most likely to prompt Internet use, and not the content of appointments (Persing, Stuart, Noyes, & Happel, 2000). This finding may also explain heightened post-search doctor utilization in high health anxious individuals (e.g., Baumgartner & Hartmann, 2011;Eastin & Guinsler, 2006;Muse et al, 2012;Singh & Brown, 2014). These doctor disadvantages, paired with the Internet's ability to reassure and reduce anxiety/uncertainty was a major reason to use online health resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the seven 1-3 relate to patient information seeking behavior; the remaining four [4][5][6][7] highlight ways in which surgeons can improve the communication of medical information to patients.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Additionally, a study in [9] found that health anxious individuals often do not care about the credibility of an online health information forum provided the information is reassuring and allays their fears. Health anxiety [10], [11], raises fears and often misconception about potential severity of ones' illnesses.…”
Section: Introductionmentioning
confidence: 99%